Effect of Bacillus megaterium on strawberry crop - Acurio-Vásconez, Ramiro Daniel (2024)
Introduction. In Ecuador, strawberry cultivation holds significant economic and social importance, having witnessed substantial growth in recent years. However, this sector faces challenges from various pests and diseases. Objective. To evaluate the effect of Bacillus megaterium on strawberry crop variables related to plant health and agronomic yield. Materials and methods. Field trial was conducted on an Albion strawberry plantation, four months after the first harvest, in Pichincha province, Ecuador. IB6 and AB4 strains of Bacillus megaterium were used at concentrations of 1 × 109 and 5 × 108 CFU/L. These were compared with a chemical control using captan (3 g/L) and chlorothalonil (2 mL/L) as fungicides, and abamectin (0.75 mL/L) and lambdacyhalothrin (0.3 mL/L) as insecticides in rotation. A split-plot design was applied with evaluations conducted at two intervals between April and June 2023. Variables measured included Botrytis cinerea incidence and severity index, fresh weight, yield, diameters, and Brix degrees of fruits. Results. There was no interaction between the treatment and time factors; the evaluated times showed no statistical differences. The treatment factor showed statistical differences for health and agronomic interest variables. The incidence of B. cinerea in the biological treatments was the lowest, with an average of 13 %. Mite control was greater than 72.71 % with the IB6 strain at a high concentration. This same treatment showed significant increases in the fresh weight of fruits (13.2 %), diameters (14 %), and soluble solids concentration (23 %), higher than the control. Conclusion. The use of Bacillus megaterium reduced the incidence of Botrytis cinerea, provided effective control against mites and thrips, and improved fresh weight, diameters and Brix degrees of fruits.